Chemical Imaging of Spatial Heterogeneities in Catalytic Solids at Different Length and Time Scales - Weckhuysen, Bert M (Angewandte Chemie (International ed.), 2009)
Catalytic solids in the spotlight: Detailed insight into the working principles of heterogeneous catalysts is essential for the design of improved or totally new ones. Such insight can be provided by making use of chemical imaging techniques, which yield spatiotemporal information about the workings of catalytic solids at different length scales: at the level of reactors, catalyst bodies, catalyst grains, and nanoparticles.Knowledge of spatiotemporal gradients in heterogeneous catalysts is of paramount importance for the rational design of new and more sustainable catalytic processes. Heterogeneities resulting in space- and time-dependent phenomena occur at different length scales; that is, at the level of catalytic reactors (mm to m), catalyst bodies (μm to mm), catalyst grains (nm to μm), and active sites and metal (oxide) particles (Å to nm). This Review documents the recent advances in the development of space- and time-resolved spectroscopic methods for imaging spatial heterogeneities within catalytic processes at these four length scales. Particular emphasis will be on the use of magnetic resonance, optical, and synchrotron-based methods, their capabilities in providing spatial resolution (1D and 2D imaging) and depth profiling (3D imaging) as well as on their time-resolved application, potential for single-molecule and nanoparticle detection, and use under reaction conditions. The Review ends with future prospects on spectroscopic markers for catalytic activity, label-free spectroscopy, tomography at the nanoscale, and correlative microscopic approaches.